Smart blind stick with voice module - K., sateesh; Kumar, prem (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, we propose a new device that assists blind people with their daily activities without depending on other people. This device will improve the confidence level of the blind people. This device is used to detect objects like solids or liquids in front of them. This proposed system uses the Arduino controller. This system detects the objects within 90 cm. An ultrasonic sensor is fixed in the stick end. This sensor senses the objects and informs the blind people through voice message. When the voice message is received from this device, the blind people can detect the objects. This system consists of three ultrasonic sensors, such as front, left, and right. This system is mainly used to identify all types of objects on the path. This proposed device is also used to identify the blind people's location and send the information to the concerned people with the help of GSM. This system is executed based upon an ultrasonic sensor.